A NEW PLANT OF THE FAMILY PLATANACEAE FROM THE EARLY PALEOGENE RECONSTRUCTED ON THE BASIS OF LEAVES AND INFLORESCENCES - Maslova N.P. (My University, 2002)
The leaves and capitate inflorescences showing macromorphological and micromorphological features of the family Platanaceae are assigned to the same plant on the basis of their joint occurrences in three Early Paleogene localities. The leaves are described as a new genus, Platimeliphyllum, and a new combination, Platimeliphyllum palanense (Budants.) N. Maslova, is proposed. The heads are assigned to a new genus, Chemurnautia, on the basis of microstructural data. These finds extend our knowledge on the morphological diversity in ancient Platanaceae and are of interest for the systematics and phylogeny of this group.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген